The association between antenatal coffee consumption and preeclampsia: a systematic review and meta-analysis - Ahmed Arafa; Masayuki Teramoto; Haruna Kawachi; Chisa Matsumoto; Saya Nosaka; Miki Matsuo; Yuka Yasui; Yuka Kato; Yoshihiro Kokubo (Komiyama Printing Co. Ltd, 2024)
Background: A growing body of evidence has documented unfavorable maternal outcomes attributed to excessive antenatal coffee consumption. Preeclampsia is one of the most common hypertensive disorders of pregnancy with several adverse maternal and neonatal outcomes. However, the association between antenatal coffee consumption and preeclampsia remains debatable. Herein, we performed a systematic review and meta-analysis of available evidence to investigate this association. Methods: After systematically reviewing PubMed and Scopus for eligible studies published until October 2023, we pooled the odds ratios (ORs) and their 95% confidence intervals (CIs) of preeclampsia for women who reported the highest versus the lowest frequencies of antenatal coffee consumption. We used the I2 statistic to measure heterogeneity across studies and the funnel plot asymmetry to assess publication bias. Results: This meta-analysis included seven retrospective studies (six case-control studies and one cross-sectional study) investigating 904 women with preeclampsia and 6,257 women without it. Combined, the highest frequencies of antenatal coffee consumption were associated with higher odds of preeclampsia: (pooled OR = 1.39, 95% CI: 1.03, 1.86), with a moderate heterogeneity across studies (I2 = 40.34% and p-value for heterogeneity = 0.122) and no publication bias (z = 0.610 and p-value for publication bias = 0.542). However, excluding the cross-sectional study, which contributed to 24.3% of the meta-analysis weight, left the association statistically non-significant: (pooled OR = 1.33, 95% CI: 0.91, 1.95; I2 = 44.59%). The association became even weaker after limiting the analysis to studies that excluded women with chronic hypertension: (pooled OR = 1.21, 95% CI: 0.77, 1.89; I2 = 41.64%) or after excluding studies with low quality: (pooled OR = 1.24, 95% CI: 0.70, 2.19; I2 = 65.79%). Conclusion: The association between antenatal coffee consumption and preeclampsia remains inconclusive. Future prospective cohort studies are needed to better investigate this association.